Drug-Coated Balloon vs. Stent for de novo Non-small Coronary Artery Disease: A Systematic Review and Meta-Analysis - Sun, Kaiwen; Liu, Zhenzhu; Wang, Hongyan (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Drug-coated balloon (DCB) has been an attractive option in de novo vessels. A systematic review and meta-analysis was conducted to evaluate the efficacy and safety of DCB versus stent for treating de novo lesions in non-small vessels. Methods: Studies in PubMed, Embase, the Cochrane Central Register of Controlled Trials and Web of Science were searched for randomized controlled trials (from their commencement to March 2021). This meta-analysis was performed by Review Manager 5.3. Results: A total of 3 random controlled trials (RCT) with 255 patients and 2 observational studies (OS) with 265 patients were included in this meta-analysis following our inclusion criteria. It could be observed that DCB presented no significant difference of cardiac death (CD) (RR 0.33, 95% CI [0.01, 8.29], P=0.50 in OS), myocardial infarction (MI) (RR 0.49, 95% CI [0.09, 2.50], P=0.39 in RCT), target lesion revascularization (TLR) (RR 0.64, 95% CI [0.19, 2.18], P=0.47 in RCT) (RR 1.72, 95% CI [0.56, 5.26], P=0.34 in OS) and late lumen loss (LLL) (SMD -0.48, 95% CI [-1.32, 0.36], P=0.26 in RCT)for de novo non-small coronary artery disease compared with stents, while minimal lumen diameter (MLD) including MLD1 (SMD -0.67, 95% CI [-0.92 -0.42], P<0.00001 in RCT) and MLD2 (SMD -0.36, 95% CI [-0.61 -0.11], P=0.004 in RCT) was smaller in DCB group. Conclusion: This systematic review showed that DCB might provide a promising way on de novo non-small coronary artery disease compared with stents. However, more RCTs are still needed to further prove the benefits of the DCB strategy.